Faktor-Faktor Yang Mempengaruhi corporate Cash Holding Pada Perusahaan Manufaktur Di Indonesia - Kurniawan, Inneke; Suhendah, Rousilita (Fakultas Ekonomi, Universitas Tarumanagara, 2019)
This study aims to examine the effect of growth opportunities, net working capital, profitability, and capital expenditures on corporate cash holding in listed manufacturing companies in Indonesian Stock Exchange period 2014-2017. This study use 54 manufacturing companies as sample in this study and also use multiple regression analysis. The results of this study indicate that profitability has a significant positive effect on corporate cash holding while growth opportunities, net working capital, and capital expenditures has a significant negative effect on corporate cash holding.